Construction Complex Departments of the Region with the Development of the Innovative Process - Abdusamatov, Baxtiyor. Koroboevich.; Abdusamatov, Shaxriyor. Baxtuyorovich. (European Journal of Life Safety and Stability (2660-9630), 2022)
The article substantiates the development of entrepreneurship as the most important factor in economic growth and quality improvement in the construction sector, the relationship between innovation and entrepreneurship and the role of innovation in managing the development of entrepreneurship in construction companies